The effect of nasal steroids on retinal nerve fiber layer in patients with a family history of glaucoma - Eski, Mehmet Tahir; Ünlü, İlhan (The European Research Journal, 2023)
Objectives: We aimed at analyzing the effect of nasal steroids on intraocular pressure (IOP) and retinal nerve fiber layer thickness (RNFL) in patients with a family history of glaucoma who also use fluticasone propionate (FP group) and mometasone furoate (MF group). Methods: Patients with a family history of glaucoma and suitable for using nasal steroids were included in the study population. IOP, anterior chamber depth (ACD), axial length (AL) and central corneal thickness (CCT) and RNFL thickness measurements of the patients were carried out. Measurements were done on 3 levels, namely, one before starting the medication, the other 1 month after starting the medication and the last one 3 months after the medication. 3 groups were established in our study: patients who are using MF group and FP group and also C group (control group; healthy individuals who have a family history of glaucoma but not using any medication). Results: The average age of patients in our study who were under medication was 33.2 ± 8.9 years. The study consisted of a total of 46 patients, 32 of whom were using nasal steroids and 14 belonging to the C group. It was found that global value in MF group decreased from 100.9 ± 7.7 to 99.6 ± 7.6 in the 3rd month and ACD in MF group decreased from 3.2 ± 0.4 mm to 2.9 ± 0.4 mm in the 1st month, both to be found statistically significant (p = 0.037 and p = 0.001 respectively). During the RNFL thickness measurements of patients, it was found that Temporal (T) segment in FP group decreased from 82.1 ± 13.8 to 81.7 ± 13.3 in the first month and T segment in MF group decreased from 72.8 ± 12.0 to 71.3 ± 10.2 in 3 months, both decreases to be found statistically significant (p = 0.047 and p=0.003 respectively). It was found that IOP in FP group increased from 15.3 ± 3.6 mm Hg to 17.7 ± 4.1 mm Hg in the 3rd month hence found to be statistically significant (p = 0.006). CCT in FP patients was found to be significantly higher in the 3rd month (p = 0.025). Conclusions: As a result of our study, it was found that nasal steroid usage in patients with a family history of glaucoma may cause an increase in IOP and thinning of the RNFL.